HUBUNGAN ANTARA PENGUASAAN POSSESSIVPRONOMEN DENGAN KETERAMPILAN MENULIS KALIMAT SEDERHANA BAHASA JERMAN - Nini Kasvia Haris; Misnah Mannahali; Muhammad Anwar (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2018)
This study aims to determine the relationship between Possessivpronomen mastery with the ability to write simple sentences for class XI students of SMA Negeri 11 Makassar. Data collection in this study was carried out with a written test. Data is analyzed by revealing product moment. The population of this study were all students of class XI IPA, with a total of 252 students. The sample of this study was 30 students of class XI Science 1 who were selected through purposive sampling technique. The results of the analysis through instant Product Moment, obtained the value of rh = (0.632)> rt = (0.361), the results showed that there was a significant positive relationship between Possessivpronomen mastery with the ability to write simple student sentences (r = 0.632).